2016
DOI: 10.1073/pnas.1521255113
|View full text |Cite
|
Sign up to set email alerts
|

Layered hydrogels accelerate iPSC-derived neuronal maturation and reveal migration defects caused by MeCP2 dysfunction

Abstract: Probing a wide range of cellular phenotypes in neurodevelopmental disorders using patient-derived neural progenitor cells (NPCs) can be facilitated by 3D assays, as 2D systems cannot entirely recapitulate the arrangement of cells in the brain. Here, we developed a previously unidentified 3D migration and differentiation assay in layered hydrogels to examine how these processes are affected in neurodevelopmental disorders, such as Rett syndrome. Our soft 3D system mimics the brain environment and accelerates ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
127
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(128 citation statements)
references
References 42 publications
(47 reference statements)
1
127
0
Order By: Relevance
“…Notably, studies in RTT mouse models have suggested that cell autonomous and non-cell autonomous mechanisms drive neuronal morphology and function [229,230,231]. In addition, recent in vitro models of RTT using MECP2 -deficient neurons derived from human pluripotent stem cells have recapitulated many neurological features of RTT [232,233,234,235,236], and have also shown neuronal migration defects [236] (Table 1). Interestingly, in contrast to the majority of the ASD-associated mTORopathies, neurons from Mecp2 −/− and Mecp2 +/− mice [43], as well as from MECP2 -deficient human pluripotent stem cells [233], show decreased mTORC1 signaling activity, transcription and protein synthesis rate.…”
Section: Mtorc1 Signaling Pathway In Monogenic Autism Spectrum Dismentioning
confidence: 99%
“…Notably, studies in RTT mouse models have suggested that cell autonomous and non-cell autonomous mechanisms drive neuronal morphology and function [229,230,231]. In addition, recent in vitro models of RTT using MECP2 -deficient neurons derived from human pluripotent stem cells have recapitulated many neurological features of RTT [232,233,234,235,236], and have also shown neuronal migration defects [236] (Table 1). Interestingly, in contrast to the majority of the ASD-associated mTORopathies, neurons from Mecp2 −/− and Mecp2 +/− mice [43], as well as from MECP2 -deficient human pluripotent stem cells [233], show decreased mTORC1 signaling activity, transcription and protein synthesis rate.…”
Section: Mtorc1 Signaling Pathway In Monogenic Autism Spectrum Dismentioning
confidence: 99%
“…Moreover, cell transplantation or explant cultures have been used to model interneuron migration in vivo or in vitro (Bellion et al, 2005; Maroof et al, 2013; Nicholas et al, 2013), but these studies have largely relied upon xenografts of human cells into immunodeficient mice. To recapitulate 3-D neuronal migration in vitro , biomaterial-based methods were recently established (Zhang et al, 2016). However, such systems still lack a physiological cellular environment, necessitating 3-D culture systems to model interneuron migration in the context of human developing cortex, which have been recently reported (Bagley et al, 2017; Birey et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Some scientists have been focused on imitating paterns, forms, textures and speciic characteristics such as mechanical resistance and chemical structure. For example, Zhang et al [33] constructed a three-dimensional system to create tissue architecture. The scafold systems were synthesised with an elastic modulus similar to brain tissue.…”
Section: Tissue Engineering and Scafold Mechanical Propertiesmentioning
confidence: 99%